Unlocking ESG Premium from Options - Cao, Jie (Jay); Goyal, Amit; Zhan, Xintong (Eunice); Zhang, Weiming (Elaine) (Journal of Financial and Quantitative Analysis, 2026)
An abstract is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.